Felicidade no ciberespaço: um estudo com jovens usuários de comunidades virtuais - Gondim, Márcio Silva (2007)
It is possible to observe the increasing of several social nets and virtual communities in the internet, what arouses intense interest of youngsters. Sites and services, which were static, get more and more dynamism and visual stimulus through images, with emphasis in attributes promoters of “happiness”. This investigation takes a look at the implications of happiness ideals in young users of communities from the technological service Orkut. We aim to detect through manifestations (expressions, images and virtual communities) the associations with attributes promoters of “happiness”. We also objectify to investigate the discourse of young users of this technological service, the ways they receive these kinds of virtual communities, interpreting the senses obtained in the use of Orkut. We also try to reflect critically about the new forms of relationship between men and several consumption signs and their repercussion while a source producer of subjectivation processes. The qualitative approach orientates this study conceptually, as it is the adequate way to understand the psychosocial phenomena which is highlighted in this research: the relation between cyberspace and “happiness” ideals. As it is an investigation of critical nature, we start epistemologically from the Critical Theory because it has a theory that has as an one of its more excellent tasks reflection, with sights to the emancipation human being, on the immediate actions of the gift in the products of the cultural industry, in search of its determinative historical and cultural. Activities with a group of young students from a private school in the city of Fortaleza (Ceará) were carried out using the (Con)text Method of Multiple Literacies, in order to collect texts about juvenile impressions related to the service Orkut. In the empirical investigation the following categories standed out: 1) Differentiation (To be distinct from the others, feeling important through compliment expressions from others); 2) Popularity (it is related to the ideal of “fame”, concerning the number of friends and fans); 3) Attractivity (relevance to determined beauty patterns). Psychosocial attributes such as beauty, differentiation and visibility (understood here as happiness ideals in the cyberspace), are more and more standed out and emphasized by Cultural Industry in the contemporaneity. This way, the identities of young members of virtual communities seem to be directly or indirectly subordinated to the apropriation of this service (while a differential consumption sign), what repercutes in the daily life of these individuals and starts to play a significative role which constitutes subjectivations. This research is concluded with an invitation to think about the possibility to create new actions and practices that can provide critical reflections and experiential spaces related to cyberspace, in a transdisciplinary context.